Properties of Stone Mastic Asphalt Incorporating Nano Titanium as Binder's Modifier - Nur Syafiqah Shamimi, Mohd Zali; Khairil Azman, Masri; Putra Jaya, Ramadhansyah; Mohd Mustafa Al Bakri, Abdullah; Muzamir, Hasan; Mohd Rosli, Mohd Hasan; Jez, Bartłomiej; Nabiałek, Marcin; Sroka, Marek; Pietrusiewicz, Paweł (Polish Academy of Sciences, 2022)
Stone mastic asphalt is a gap-graded mix and is usually related to its high bitumen content and its skeleton-like constitution. Although famous for its durability, high resistance to fatigue and rutting, issues such as bleeding and premature aging do occur in the mix since it has a high bitumen content and voids due to its gap-graded structure. In order to encounter these problems from affecting the mix, some instances such as adding additives, rejuvenators and stabilizers into the mixture has been implemented.